2019
DOI: 10.4103/jfmpc.jfmpc_382_18
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practices related to burn first aid among Majmaah community, Saudi Arabia

Abstract: Background:Burns in developing countries account for significant morbidity and mortality which have been shown by increasing burn first aid awareness. In general, flames, scalds, and contact burns are the most common causes, but in children scalds are the most common.Objectives:This study aims to assess the general knowledge and practices related to burn first aid among Majmaah community.Methods:This study is a cross-sectional study. Data were collected in 2018 using convenience sampling technique. Saudi men a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 25 publications
(25 reference statements)
4
18
2
5
Order By: Relevance
“…Almost all participants in the study (98.5%) sought medical assistance directly. 14 According to the global reports, community first aid knowledge for burns is rather limited, especially in developing and underdeveloped countries. 15,16,17 A study by Graham et al that investigated knowledge of parents in Southern of Yorkshire, Britain indicated and found that less than half of the parents are aware of the first aid for burns.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all participants in the study (98.5%) sought medical assistance directly. 14 According to the global reports, community first aid knowledge for burns is rather limited, especially in developing and underdeveloped countries. 15,16,17 A study by Graham et al that investigated knowledge of parents in Southern of Yorkshire, Britain indicated and found that less than half of the parents are aware of the first aid for burns.…”
Section: Discussionmentioning
confidence: 99%
“…Yanıkta doğru ve hemen yapılan ilkyardım müdahalesi ağrıyı ve doku hasarı boyutunu önemli ölçüde azaltarak yanık iyileşmesini hızlandırmakta ve hayatta kalma oranını artırmaktadır (3,12,14). Yanıkta ilk yardım uygulamalarını araştıran güncel kanıtlar yanık yarasına su dışında hiçbir şeyin uygulanmaması gerektiğini, yanık bölgesinin yaralanmadan sonraki ilk 3 saat içinde 20 dakika 2-15 0 C akan suda tutulmasının yanıkta en uygun ilkyardım müdahalesi olduğunu bildirmektedir (5,6,12,14,16,17).…”
Section: Discussionunclassified
“…Bu sürede yapılan doğru ve etkin ilk yardım müdahalesi yanık alanında ağrıyı, doku hasarı boyutunu, hastanede kalış süresini ve ölüm oranlarını azaltmakla birlikte epitel hücrelerin hızla çoğalmasını sağlayarak yanık iyileşmesini de hızlandırmaktadır (3,10,11). Ancak yapılan çalışmalarda yanmış çocuklara hastane öncesi doğru ve yeterli ilk yardımda bulunulmadığı, yanık yarasında ağrıyı azaltmak ve iyileştirmek amacıyla su kullanımının yetersiz olduğu, motor yağı, salça, tereyağı, dilimlenmiş patates, diş macunu gibi geleneksel tedavi yöntemlerinin ise yaygın olarak kullanıldığı bildirilmektedir (3,4,7,8,(12)(13)(14)(15). Literatürden elde edilen bu bulgular annelerin yanıkta ilkyardım bilgisinin yetersiz olduğunu göstermektedir.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In Saudi Arabia, studies reported inadequate level of knowledge of general population of first aid in burns emergencies including communities of Al-Madinah Al-Munawara, Jeddah, Riyadh, Majmaah and Hail [10][11][12][13][14]. Among Medical Students, King Khalid University in Abha and Princess Norah University in Riyadh, studies showed poor knowledge about first aid among the medical students [15][16][17].…”
Section: Introductionmentioning
confidence: 99%